Electrochemical Detection of Environmental Pollutants Based on Graphene Derivatives: A Review - Kumunda, Coster; Adekunle, Abolanle S.; Mamba, Bhekie B.; Hlongwa, Ntuthuko W.; Nkambule, Thabo T. I. (Frontiers in Materials, 2021)
Population-driven socioeconomic urban expansion, industrialization, and intensified modern agricultural practices are interlinked to environmental challenges culminating in compromised water quality due to pollution by toxic, persistent, and bioaccumulative heavy metal ions, pesticides, nitroaromatics, and other emerging pollutants. Considering the detrimental impact of pollutants on human health and ecosystem, their detection in different media including water is paramount. Notably, electrochemical techniques are more appealing owing to their recognized advantages. This research summarizes and evaluates the most recent advances in the electrochemical sensing of environmental pollutants such as heavy metal ions, pesticides, nitroaromatics, and other distinct emerging contaminants. Besides, the review focuses on the application of electrochemical detection of the selected pollutants through analysis of representative reports in the five years from 2016 to 2020. Therefore, the review is intended to contribute insights and guidelines to contemporary progress in specific electrochemical application practices based on graphene derivatives, toward the aforenamed pollutants. Thus, it focused on sensing methods such as cyclic voltammetry, anodic stripping voltammetry, and electrochemical impedance spectroscopy employing different sensing elements incorporating graphene. Moreover, the review also highlighted graphene synthesis pathways, sensor design strategies, and functionalization. Furthermore, the review showed that there is congruence in the literature that functionalized graphene and its derivatives remain as viable modifiers in electrochemical sensing of pollutants. Nonetheless, the study also appraised the absence of literature reports on electrochemical detection of natural organic matter substances like humic acid and fulvic acid using a graphene-based sensor. In reckoning, current challenges related to graphene synthesis and applicability, envisaged opportunities, and future perspectives are outlined.